(untitled) (Nigerian Journal of Health Sciences, 2023)
Background: Although the maxillofacial region is very rich in blood supply, surgical wounds in this region are also prone to infection, if good aseptic techniques are not strictly followed. There is a need to evaluate healing of surgical wound following the removal of wound dressing at different days postoperative in the maxillofacial region. This paper describes and compares healing in terms day of exposing a clean surgical wound. Objective: To evaluate healing of surgical wound following the removal of wound dressing at different days postoperative in the maxillofacial region. Materials and Methods: One hundred and fifteen patients who met inclusion criteria, admitted for surgeries in maxillofacial regions were randomly grouped into one of the five surgical dressing options. ASEPSIS wound scoring system was used for the study. All patients were monitored for a period of 7 days when wound healing and suture removal is expected to take place uneventfully. Chi‑square, Fisher’s exact, and nonparametric Kruskal–Wallis tests as appropriate. Statistical significance was set at P < 0.05. Results: There was no difference in healing between males and females (χ2 = 2.832, df = 4, P = 0.586). There was no significant difference in healing within the different days of exposure of the wound (χ2 = 8.479, df = 4, P = 0.076). Conclusion: Early exposure of surgically clean wounds does not impair healing.